2018
DOI: 10.1186/s12886-018-0755-9
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal imaging of foveoschisis and macular pseudohole associated with gyrate atrophy: a family report

Abstract: BackgroundTo report the results of multimodal imaging of a biochemically confirmed case of a family with gyrate atrophy (GA) associated with foveoschisis and macular pseudohole.Case presentationTwo sisters presented to us with progressive bilateral decreased vision. The 26-year old sister had a best corrected visual acuity (BCVA) of 20/32 in the right eye (RE) and 20/100 in the left eye (LE). Dilated fundus examination revealed multiple bilateral chorioretinal atrophy areas in the midperipheral and peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 20 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…16 For far advanced disease, PPV with silicone oil tamponade has been shown to be effective in maintaining or achieving good visual outcomes. 13,[17][18][19] Retinoschisis or macrocyst associated with Coats disease has been described earlier. One patient in the cohort was reported previously by our group, 12 and Berinstein et al described 2 cases of peripheral and central schisis but did not comment on the interval change in the clinical features during its management.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…16 For far advanced disease, PPV with silicone oil tamponade has been shown to be effective in maintaining or achieving good visual outcomes. 13,[17][18][19] Retinoschisis or macrocyst associated with Coats disease has been described earlier. One patient in the cohort was reported previously by our group, 12 and Berinstein et al described 2 cases of peripheral and central schisis but did not comment on the interval change in the clinical features during its management.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, it is thought that leakage, hypoxia, and toxicity to the retinal pigment epithelial cells likely play a role in cavity development. 13 Our clinical series follows 18 patients with clinical and photographic diagnoses of Coats disease with acquired retinoschisis. Our study supports the idea that treatment of the abnormal vasculature may lead to resolution of the schisis, and therefore vascular leakage and exudation may play a role in its development.…”
Section: Discussionmentioning
confidence: 99%
“…The current literature on the treatment of foveoschisis in GA is scarce. Zhioua Braham et al reported a 26-year-old female affected by GA with foveoschisis which showed poor response to arginine-restricted diet and vitamin B6 supplementation (300 mg/day) treatment for 6 months [ 7 ]. For our patient, foveoschisis showed partial regression after 3 weeks’ high-dose vitamin B6 treatment without an arginine-restricted diet, but the plasma ornithine levels and BCVA remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Macular involvement has been reported including cystoid macular edema (CME), epimacular membrane, macular hole, choroidal neovascularization and foveoschisis [ 3 , 4 ]. Foveoschisis is rare in GA with only three cases reported previously [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This was the first report describing the use of bevacizumab to treat this condition. The pathogenesis of CME associated with GA is still unknown, however, new data from optical coherence tomography angiography suggest that retinal ischemia and vascular alterations may play a role, and indicate that anti vascular endothelial growth factor agents, such as bevacizumab, could be useful [ 2 , 3 ]. Previously, intravitreal triamcinolone acetonide has been shown to improve CME associated with GA [ 4 ].…”
Section: Dear Editormentioning
confidence: 99%